(untitled) (Journal of Environmental Bioremediation and Toxicology, 2014)
Acetylcholinesterase (AChE) assay is among the most rapid, simplest and economic assay in existence. AChE is known to be inhibited strongly by heavy metals aside from insecticides. Its use as an inhibitive assay for heavy metals is less well known. We report on the AChE from Periophtalmodon schlosseri as a sensitive assay for heavy metal ions. Heavy metals exhibited exponential decay type inhibition curves with calculated IC50 for copper, mercury, chromium and arsenic at 0.088, 0.371, 0.112 and 0.141 mg l-1, respectively. The LOD for copper, mercury, chromium and arsenic were 0.093, 0.126, 0.099 and 0.127 mg l-1, respectively. The LOQ for copper, mercury, chromium and arsenic were 0.001, 0.209, 0.103 and 0.219 mg l-1, respectively. The IC50sfor these heavy metals are lower than the values for immobilised urease, Daphnia magna, MicrotoxTM,rainbow trout, papain and bromelain assays.